2014
DOI: 10.1590/1809-4503201400040017
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors in patients with Non-Small Cell Lung Cancer treated in private health care

Abstract: The outcomes described are favorably similar to the current literature from developed countries. Besides the better access to health care in the private insurance scenario, most patients are still diagnosed in late stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
4
13
0
9
Order By: Relevance
“…The magnitudes and directions of the estimated effects related to these factors in the present study are consistent with those reported in other studies and will be addressed below 6 18 , 19 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitudes and directions of the estimated effects related to these factors in the present study are consistent with those reported in other studies and will be addressed below 6 18 , 19 …”
Section: Discussionsupporting
confidence: 90%
“…A review of the literature revealed two survival studies of patients with non-small cell lung cancer, both of which were conducted in the city of Rio de Janeiro, Brazil: one in a public hospital, in which 60-month survival probabilities were estimated 6 ; and one in a private clinic, 19 in which 24-month survival probabilities were estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in Brazil have reported median OS similar to our findings (Araujo et al., 2014; Younes, Pereira, Fares, & Gross, 2011). The median OS of 25.5 months in our Taiwanese cohort could be the result of frequent and appropriate therapy with EGFR TKIs for patients with EGFR ‐positive status, since gefitinib was approved for first‐line therapy of EGFR ‐positive NSCLC in Taiwan in June 2011.…”
Section: Discussionmentioning
confidence: 99%
“…A study that aimed to describe the characteristics, treatments and survival of lung cancer patients identified that 59.9% of the patients received palliative therapy. It is reiterated that, of those mentioned, most of the 236 patients presented diagnosis in advanced stages (6) . In this study, all of the patients had clinical stage IV, and lung cancer cases accounted for 6.5%.…”
Section: Alcohol and Tobacco Consumption Became A Constantmentioning
confidence: 98%
“…Once called "individual risk factors," they now have broader approaches that favor the profile of access to public policies, consumption patterns and social interaction networks (5) . Despite major advances in cancer treatment, healing is not always possible and the result is shown in the ascending slope of incidence and mortality of cancer cases in Brazil (6) . With this scenario, the World Health Organization (WHO) increasingly recommends that the approach to people in later life be programmed and planned in order to comprehensively meet the multiplicity of problems presented (7) .…”
Section: Introductionmentioning
confidence: 99%